Sorafenib enhances pemetrexed cytotoxicity through an autophagy- dependent mechanism in cancer cells - Bareford, M Danielle (Landes Bioscience, 2011)
Pemetrexed (ALIMTA) is a folate anti-metabolite that has been approved for the treatment of non-small cell lung cancer, and has been shown to stimulate autophagy. In the present study, we sought to further understand the role of autophagy in the response to pemetrexed and to test if combination therapy could enhance the level of toxicity through altered autophagy in tumor cells. The multikinase inhibitor sorafenib (NEXAVAR), used in the treatment of renal and hepatocellular carcinoma, suppresses tumor angiogenesis and promotes autophagy in tumor cells. We found that sorafenib interacted in a greater than additive fashion with pemetrexed to increase autophagy and to kill a diverse array of tumor cell types. Tumor cell types that displayed high levels of cell killing after combination treatment showed elevated levels of AKT, p70 S6K and/or phosphorylated mTOR, in addition to class III RTKs such as PDGFRβ and VEGFR1, known in vivo targets of sorafenib. In xenograft and in syngeneic animal models of mammary carcinoma and glioblastoma, the combination of sorafenib and pemetrexed suppressed tumor growth without deleterious effects on normal tissues or animal body mass. Taken together, the data suggest that premexetred and sorafenib act synergistically to enhance tumor killing via the promotion of a toxic form of autophagy that leads to activation of the intrinsic apoptosis pathway, and predict that combination treatment represents a future therapeutic option in the treatment of solid tumors.